The Social Impact of Creative Arts in Australian Communities - Gattenhof, Sandra; Hancox, Donna; Klaebe, Helen; Mackay, Sasha; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book brings together discussions about Australian arts policy and funding, outcomes of arts engagement in terms of social inclusion, well-being, and education. It presents exemplars of creative programs or case studies that build capacity and lasting impact for communities in urban and regional Australia. This book describes the impact of the arts using narrative case studies. Through this, it develops conceptual understanding and frameworks that can be used to dynamically assess the value and impact of arts engagement across the three types of cultural value: intrinsic value, instrumental value, and institutional value. It focuses on how arts engagement creates, supports, and extends factors such as well-being, social inclusion, and educational achievement. This book provides an innovative examination of the evidence from Australian projects depicting the impact of the arts on a range of indicators and sectors.
1 Introduction -- 2 Understanding social impact in the Australian context -- 3 Sidelined evaluation -- 4 Using theatre to stimulate difficult conversations in regional communities -- 5 Arts-based methodologies for fostering inclusion and understanding within diverse communities -- 6 Using dance to promote wellbeing and prosocial behaviours in early education settings -- 7 Collaborative design with communities for impact assessment -- 8 Co-creative art and meaningful community participation -- 9 Community engagement at a distance: testing digital methods during COVID-19 lockdown -- 10 Conclusion.
Keywords: Art$1 (BStudy and teaching.s; Education and state; Education$1 (BCurricula.s; Educational sociology; Creativity and Arts Education; Educational Policy and Politics; Curriculum Studies; Sociology of Education